Răspuns:
a) IxI<2;
-2<x<2 => x=(-2,2)
b) Ix-2I[tex]\leq[/tex]3;
-3[tex]\leq[/tex]x-2[tex]\leq[/tex]3 I+2
-1[tex]\leq[/tex]x[tex]\leq[/tex]5 => x=[-1,5]
c) I1-xI<=0;
d) -15 Ix-1I>-105;
-15 Ix-1I>-105 I+15
Ix-1I>90
-90>x-1>90 I+1
-89>x>91 => x=(-89,91)
e) 3-I4x-1I[tex]\geq[/tex]0;
3-I4x-1I[tex]\geq[/tex]0 I-3
-I4x-1I[tex]\geq[/tex]-3 I x(-1)
I4x-1I[tex]\leq[/tex]3
-3[tex]\leq[/tex]4x-1[tex]\leq[/tex]3 I+1
-2[tex]\leq[/tex]4x[tex]\leq[/tex]4 I :4
-2/4[tex]\leq[/tex]x[tex]\leq[/tex]1 => x=(-2/4,1)
f) IxI x (x-4)>0;
IxI apartine lui N;
x-4>0 I+4
x>4 => x=(-infinit, 4)
Explicație pas cu pas:
Sper sa fie corect